Managerial perception among professional football players and a review of the relationships between football players and managers - (:unkn) unknown (SILA SCIENCE, 2012)
This study aimed to determine the attitudes of professional football players towards manager ship perception and manager ship practices and relationships. In addition, it was also aimed to investigate football players in terms of their age, the league they are playing in, duration of sports participation and participating in the national team and to identify the differences between them. 96 football players playing in professional clubs participated in the study. Of these participants, 29 played in Sport Toto Super League, 33 in Bank Asya 1. League and 34 football players played in Sport Toto League 2. This research used a two-part questionnaire form of which reliability was tested (Cronbach Alpha = 0.70). The collected data was analyzed on a computer and chi-square test was used for the relationships between the variables. According to the results of the study, there is a statistically significant difference between the league levels of players and their mean scores of the judgments managers are needed for professional development and managers have major influence on players success and also between the participating in the national team and mean scores of managers should be given authority to sign on behalf of players (p < 0.05). There is no statistically significant difference between education levels of footballers and their managerial judgments (p > 0.05). Accordingly, it can be suggested that education levels and these judgments are independent of each other. As a result, managerial position is really important and necessary for professional development and success of a football player.
Keywords: Professional football; Managership; Managerial perception; Manager relationship; ORGANIZATIONAL COMMITMENT; SATISFACTION; SPORT